Using item response theory for the development of a new short form of the Guilford-Zimmerman Temperament Survey - Looti, Mohammed; Abd-Alzim, Marwa (Journal of Indonesian Psychological Science (JIPS), 2025)
The Guilford-Zimmerman Temperament Survey (GZTS) is a widely used personality inventory; however, its length (300 items) poses a significant drawback in many assessment contexts. This paper presents two studies that employed Item Response Theory (IRT) to develop a psychometrically robust short form of the GZTS (GZTS-SF), specifically designed for university students. Study 1 involved 850 students who completed the full version of the GZTS. Using the 2-Parameter Logistic (2PL) IRT model, items were selected based on optimal discrimination and difficulty parameters, ensuring comprehensive coverage across all ten GZTS traits. Items exhibiting differential item functioning (DIF) across gender were removed to enhance measurement fairness.Study 2 evaluated the resulting 100-item GZTS-SF using a separate sample of 400 university students. The short form demonstrated reliability coefficients that were comparable to or better than those reported for existing short forms, high correlations with the corresponding full-scale GZTS scores, and strong convergent and discriminant validity when assessed against the Big Five Inventory (BFI). Exploratory Structural Equation Modeling (ESEM) further supported the ten-factor structure of the GZTS-SF. Overall, the GZTS-SF offers a more efficient yet psychometrically sound method for assessing the ten GZTS traits, making it highly suitable for research and applied contexts involving university populations. KEY WORDS: response theory; short form development; personality assessment; psychometric evaluation, GZTS Copyright ©2025. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0